2015
DOI: 10.1038/nm.3883
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of resident memory T cells in protective immunity and inflammatory disease

Abstract: Over the past decade, it has become clear that there is an important subset of memory T cells that resides in tissues — tissue resident memory T cells (TRM). There is an emerging understanding that TRM have a role in human tissue specific immune and inflammatory diseases. Furthermore, the nature of the molecular signals that maintain TRM in tissues is the subject of much investigation. In addition while it is logical for TRM to be located in barrier tissues at interfaces with the environment in human and mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
449
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(467 citation statements)
references
References 124 publications
9
449
1
2
Order By: Relevance
“…Although lymphocytes are best characterized in the blood, lymphatic fluid, and lymphoid organs, interest in tissue-resident lymphocytes is currently emerging (33)(34)(35)(36)(37). Different lymphocyte populations have now been described in several nonlymphoid organs, where they can influence the local molecular milieu and modulate other resident cells (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Although lymphocytes are best characterized in the blood, lymphatic fluid, and lymphoid organs, interest in tissue-resident lymphocytes is currently emerging (33)(34)(35)(36)(37). Different lymphocyte populations have now been described in several nonlymphoid organs, where they can influence the local molecular milieu and modulate other resident cells (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of cell surface markers CD69 and CD27 suggested significantly higher levels of Vα2.3 + Vβ22 + T-cells to be activated, and also to be differentiated to a higher degree compared to their Vα2.3 − Vβ22 − CD4 + T-cells counterparts, likely reflecting antigenic stimulation. Alternatively, the high CD69 expression reflects a tissue-resident memory T-cell phenotype, suggested to be of importance for human tissue-specific immune and inflammatory diseases [25].…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of T cells in peripheral tissues after resolution of inflammation is a hallmark of resident memory T cells (T RM cells) (11). T RM cells are generated by immune challenges in peripheral tissues, provide rapid responses to rechallenge, and persist in the absence of antigen (12). Studies using mouse infection models have demonstrated that immune challenges in skin, whether they are infectious or hapten driven, lead to colonization of the entire skin surface with antigen-specific T RM (13,14).…”
Section: Putative Pathogenic T Cell Clones Utilize a Skewed Tcr Vα Rementioning
confidence: 99%